Specific features of family entrepreneurship in agriculture - Lea Kubíčková; Markéta Fišerová (Trends Economics and Management, 2019)
Purpose of the article: The purpose of the paper is to define the specific features of Czech family businesses operating in agriculture, identify the main problem areas and advantages that family farms subjectively perceive in this form of entrepreneurship. Methodology/methods: In order to define the specific features of family entrepreneurship in agriculture, it was necessary to obtain data from family farms. Thus, in 2018, primary data were collected using in-depth interviews with the selected family farm owners or other family members in the Czech Republic. Scientific aim: The scientific objective of the paper is to define the specifics of Czech family business in agriculture, as this topic is not described in detail in the scientific literature and the situation of Czech family farms is different from that of foreign family farms, to which more space is devoted in the scientific literature. Findings: The authors identify the subjectively perceived benefits as well as problem areas of family entrepreneurship in agriculture through in-depth interviews conducted on 11 family farms. The main advantages as seen by Czech family farms include the individual planning of their working time, family flexibility, working from home, and spending time with their families. The respondents also emphasize the positive attitude to working on a family farm. The main disadvantages include overlapping of personal and working relationships, financial situation, dependence on weather, the lack of land, and the lack of support from the state. Conclusions: Overall, the subjectively perceived advantages of family entrepreneurship prevail, which fully corresponds with the findings of the AMSP CR survey although it should be noted the family farm owners have also reported in detail about the downsides of this business.
Keywords: M15; M21; 650; family entrepreneurship; agriculture; advantages and disadvantages of family entrepreneurship